Corporate Strategy and Product InnovationCorporate Strategy and Product Innovation, RothbergRobert R.. New York: The Free Press, 1976. 518 pp., $13.95. - Witteried, George C. (Academy of Management Review, 1978)
The article reviews the book ?Corporate Strategy and Product Innovation,? edited by Robert R. Rothberg.